Deconvolution of monocyte responses in inflammatory bowel disease reveals an IL-1 cytokine network that regulates IL-23 in genetic and acquired IL-10 resistance - Aschenbrenner, D; Quaranta, M; Banerjee, S; Ilott, N; Jansen, J; Steere, B; Chen, Y-H; Ho, S; Cox, K; Arancibia-Cárcamo, CV; Coles, M; Gaffney, E; et al. (BMJ, 2020)
OBJECTIVE: Dysregulated immune responses are the cause of IBDs. Studies in mice and humans suggest a central role of interleukin (IL)-23-producing mononuclear phagocytes in disease pathogenesis. Mechanistic insights into the regulation of IL-23 are prerequisite for selective IL-23 targeting therapies as part of personalised medicine.